Adaptive Physiological Response of Parthenium hysterophorus to Elevated Atmospheric CO2 Concentration - Singh, Hukum; Sharma, Rupali; Savita,; Singh, Madan Prasad; Kumar, Manoj; Verma, Amit; Ansari, Mohammad Wahid; Negi, Mridula; Sharma, Satish Kant (Indian Forester, 2018)
Parthenium hysterophorus, a harmful weed, is a potential threat to agricultural productivity of various crops. An experiment was performed to analyze the physiological adaptation of P. hysterophorus grown under ambient and elevated atmospheric CO2 concentration (800 Î¼ mol mol-1 ) using Open Top Chamber (OTC) approach. Under elevated CO2 conditions, it showed improved plant height and diameter, leaf fresh and dry weight, leaf moisture content, leaf length and leaf area, root length, leaf area index, specific leaf area, shoot fresh and dry weight, root fresh and dry weight and total dry biomass as compared to plants retained under ambient condition. Likewise, the photosynthetic rate and water use efficiency was also increased. The elevated CO2 had profound impact on reduction of stomatal conductance and transpiration rate of plants when compared to ambient conditions. The present findings suggest that elevated CO2 mediated improved intrinsic water use efficiency; intercellular CO2 concentration, intrinsic carboxylation efficiency, intrinsic mesophyll efficiency, biomass production and tissue carbon allocation which prolongs plant growth and development, and thereby better weed adaptability under changing climatic scenario especially rising atmospheric CO2 concentration. Thus, P. hysterophorus spread requires major concern in biological research to restrict its expansion in future predicted climate change scenario to sustain agricultural as well as forest productivity.